Evaluation of risk factors in women attending a sexually transmitted infection clinic at a tertiary care centre - Chaudhary, Nisha; Kalyan, Rajkumar; Agarwal, Jyotsna; Singh, Mastan; Qureshi, Sabuhi (International Journal of Research in Medical Sciences, 2018)
Background: Reproductive tract infections (RTIs) continue to present major health, social and economic problems all over the world and their complications are the most important causes of morbidity and mortality for women especially in the developing countries. Interest in RTIs and their management has increased tremendously because presence of a RTI in the sexual partner increases the risk of acquisition of HIV. Aim was to evaluate the risk factors in women attending a sexually transmitted infection clinic at a tertiary care centre and prevalence of RTI in our setup. Methods: The present study was conducted on 318 women of reproductive age group (18-45 years) attending the Reproductive tract infection/ sexually transmitted infection (RTI/STI) clinic at our tertiary care centre, they were evaluated for the prevalence of following RTIs: chlamydia, gonorrhoea, syphilis, bacterial vaginosis, trichomoniasis and candidiasis; and their correlation with clinical features and associated risk factors. Results: The factors found to be significantly associated with RTI were illiteracy, unemployment, past history of RTI in patient and presence of RTI in their partner. The prevalence of RTI in our setup reported 9.7%. The prevalence of candidiasis was maximum (11.5%) followed by chlamydia (4.1%), syphilis (4.1%), bacterial vaginosis (1.73%) and trichomoniasis (0.57%). Conclusions: None of the women was found positive for gonorrhoea. No coexistence of any two diseases found in any patient. Most common presentation was genital discharge (52.8%) followed by lower abdominal pain (45.2%).